A Holistic Approach to COVID-19: Prediction to Prevention - Kathan Gandhi, VenkatsaiSiddeshPadala, Dr.D.V.Pushpalatha, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Throughout history, humans have faced pandemics that impact the social and economic landscape and drive innovation to overcome the crisis. The COVID-19 pandemic has affected many individuals, impacted the global economy, changed social interaction, and created pressure to find a solution. This paper provides a comprehensive review that aims to help in achieving the goal of prediction, prevention, and monitoring of the global pandemic. Various data analysis methods that use available pandemic information to project future cases and deaths have been demonstrated. Similarly, spatial investigations that visually describe the transmission of the disease and indicate the similarities between infected regions have been shown. Additionally, specific environmental factors that affect the diffusion of the coronavirus have been described. Furthermore, prevention techniques and guidelines are discussed. Then, IoT’s potential in monitoring the disease, helping patients, and contributing to healthcare is highlighted. Finally, the paper provides a concluding interpretation of the pandemic problem and makes recommendations.